2023
DOI: 10.1002/cac2.12411
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived insulin‐like growth factor‐binding protein‐1 contributes to resistance of hepatocellular carcinoma to tyrosine kinase inhibitors

Abstract: Background Antiangiogenic tyrosine kinase inhibitors (TKIs) provide one of the few therapeutic options for effective treatment of hepatocellular carcinoma (HCC). However, patients with HCC often develop resistance toward antiangiogenic TKIs, and the underlying mechanisms are not understood. The aim of this study was to determine the mechanisms underlying antiangiogenic TKI resistance in HCC. Methods We used an unbiased proteomic approach to define proteins that were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Guo et al also demonstrated that YRDC, which was capable of binding transfer RNA (tRNA), was related to acquired resistance to LEN through regulation of the protein translation of KRAS through the modification of tRNA [ 26 ]. We also previously reported the acquired resistance mechanism of LEN due to the insulin-like growth factor-binding protein-1 (IGFBP-1) protein [ 27 ]. IGFBP1 is promoted by LEN-induced ischemia, and it could induce neo-angiogenesis in a VEGF-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al also demonstrated that YRDC, which was capable of binding transfer RNA (tRNA), was related to acquired resistance to LEN through regulation of the protein translation of KRAS through the modification of tRNA [ 26 ]. We also previously reported the acquired resistance mechanism of LEN due to the insulin-like growth factor-binding protein-1 (IGFBP-1) protein [ 27 ]. IGFBP1 is promoted by LEN-induced ischemia, and it could induce neo-angiogenesis in a VEGF-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic cells can prevent hypoxia by activating the HIF pathway and modifying the TME to adapt to hypoxic conditions. Furthermore, hypoxia is closely associated with tumour proliferation and acquired resistance to various therapies 99,100 …”
Section: Possible Mechanisms Of Resistance To Lenvatinibmentioning
confidence: 99%
“…In addition, they found that the combination of the FACT complex inhibitor curaxin and VEGF antibody drugs (e.g., lenvatinib, bevacizumab) showes an excellent synergistic effect and enhances the anticancer effect of antiangiogenic therapy. Furthermore, the combination of lenvatinib with IGFBP‐1 neutralizing antibodies or integrin α5β1 inhibitors could inhibit hypoxia‐induced IGFBP‐1 and downstream integrin α5β1/FAK/ERK signalling, resulting in significantly improved drug resistance 100 . For abnormal metabolic alterations, including increased glucose metabolism and increased cholesterol synthesis in CSCs, appropriate inhibitor combinations can substantially inhibit tumour growth by restoring lenvatinib sensitivity in HCC; these inhibitors include PFKFB3 silencers, PFKFB3 suppressors (i.e., PFK15), and the cholesterol‐lowering drug simvastatin 114,116 …”
Section: Strategies To Improve Lenvatinib Efficacymentioning
confidence: 99%
See 2 more Smart Citations